CEP55 is a determinant of cell fate during perturbed mitosis in breast cancer. Issue 9 (14th August 2018) - Kalimutho, Murugan; Sinha, Debottam; Jeffery, Jessie; Nones, Katia; Srihari, Sriganesh; Fernando, Winnie C; Duijf, Pascal HG; Vennin, Claire; Raninga, Prahlad; Nanayakkara, Devathri; Mittal, Deepak; Saunus, Jodi M; et al.
Abstract: The centrosomal protein, CEP55, is a key regulator of cytokinesis, and its overexpression is linked to genomic instability, a hallmark of cancer. However, the mechanism by which it mediates genomic instability remains elusive. Here, we showed that CEP55 overexpression/knockdown impacts survival of aneuploid cells. Loss of CEP55 sensitizes breast cancer cells to anti‐mitotic agents through premature CDK1/cyclin B activation and CDK1 caspase‐dependent mitotic cell death. Further, we showed that CEP55 is a downstream effector of the MEK1/2‐MYC axis. Blocking MEK1/2‐PLK1 signaling therefore reduced outgrowth of basal‐like syngeneic and human breast tumors in in vivo models. In conclusion, high CEP55 levels dictate cell fate during perturbed mitosis. Forced mitotic cell death by blocking MEK1/2‐PLK1 represents a potential therapeutic strategy for MYC‐CEP55‐dependent basal‐like, triple‐negative breast cancers. Synopsis: By integrating analyses of multiple in vitro and in vivo breast cancer models, this study provides direct evidence for CEP55‐mediated protection of aneuploidy. Targeting MEK1/2‐PLK1 axis in CEP55‐MYC‐dependent basal‐like, triple‐negative breast cancers could be a novel treatment strategy. CEP55 overexpression is associated with poor clinical outcomes in breast cancer. CEP55 dictates cell fate during perturbed mitosis. High levels of CEP55 are protective in aneuploid cells. Loss of CEP55 primes premature CDK1/Cyclin B activation and apoptosis upon treatment with anti‐mitotic drugs. Cep55 is a marker for rationale use of combined MEK1/2‐PLK1 inhibition in triple‐negative breast cancers. Abstract : By integrating analyses of multiple in vitro and in vivo breast cancer models, this study provides direct evidence for CEP55‐mediated protection of aneuploidy. Targeting MEK1/2‐PLK1 axis in CEP55‐MYC‐dependent basal‐like, triple‐negative breast cancers could be a novel treatment strategy.